Incidence of sexually transmitted infections in adolescents between 13 to 19 years old residents in the municipality of Cascavel between the years 2010 to 2020 - Paltanin, Sinara Vidotti (2022)
STIs (Sexually Transmitted Infections) have emerged as rising agents in the spread of sexually transmitted diseases among adolescents. Thus, this study aims to sample the number of adolescents aged between 13 and 19 years old residing in the city of Cascavel between 2010 and 2020 who presented, during the period under analysis, some sexually transmitted infection and sought treatment and medical advice at any health unit. For this, a descriptive quantitative methodology was used, analyzing the obtained data and presenting them in graphics in an explanatory and descriptive way. The survey pointed out as main results that 67.71% of patients who had some STI are male; 50% were white; of the young population between 10 and 19 years old who had a positive diagnosis for some STI, 96.34% was between 15 and 19 years old; 6% of the total population who had a positive diagnosis for some STI, was between 10 and 19 years old. By obtaining real data present in the population of adolescents in the city of Cascavel, government entities and their respective educational and health sectors will be able to work together, guided and substantiating subsidies that will structure and direct efficient actions for the control and extermination of STIs in the County.